Science with Herschel: Results from the HERITAGE project. Issue 5 (June 2014) - Meixner, M.; Seale, J.; Roman‐Duval, J.; Gordon, K.; the HERITAGE Team
Abstract The Herschel Space Observatory completed its last observation on 2013 April 29 after completing 35000 astronomical observations resulting in numerous discoveries. In this review, we describe the capabilities and general scope of the Herschel mission. In particular, we review the science results from one of the open time key programs, the HERschel Inventory of The Agents of Galaxy Evolution (HERITAGE) in the Magellanic Clouds. The HERITAGE project mapped the Large Magellanic Cloud (LMC) and Small Magellanic Cloud (SMC) at 100, 160, 250, 350, and 500 μm using the SPIRE/PACS parallel mode. The total global fluxes for the LMC and SMC agree with measurements by other missions, including Planck. The HERITAGE maps of the LMC and SMC are dominated by the ISM dust emission and bear most resemblance to the tracers of ISM gas rather than the stellar content of the galaxies. The overriding science goal of HER‐ITAGE is to study the life cycle of matter as traced by dust in the LMC and SMC. The far‐infrared and submillimeter emission is an effective tracer of the interstellar medium (ISM) dust, the most deeply embedded young stellar objects (YSOs) and the dust ejected by the most massive stars which are discussed briefly in this review. The HERITAGE team has delivered the maps and source catalogs created for each of the 5 bands to the Herschel Science Center archive which will hold the legacy of Herschel. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)